1996
DOI: 10.1073/pnas.93.15.7577
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 nucleocapsid protein induces "maturation" of dimeric retroviral RNA in vitro.

Abstract: After a retrovirus particle is released from the cell, the dimeric genomic RNA undergoes a change in conformation. We have previously proposed that this change, termed maturation of the dimer, is due to the action of nucleocapsid (NC) protein on the RNA within the virus particle. We now report that treatment of a 345-base synthetic fragment of Harvey sarcoma virus RNA with recombinant or synthetic HIV-1 NC protein converts a less stable form of dimeric RNA to a more stable form. This phenomenon thus appears to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
149
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(158 citation statements)
references
References 27 publications
9
149
0
Order By: Relevance
“…There are five amino acids which differ between the two finger sequences. These include (finger one to finger two): F to W, N to K, I to Q, A to M, and N to D at positions 16,17,24,25, and 27 of finger one, respectively. NC point mutants were constructed where the amino acid residues in finger one were incrementally replaced by those at the corresponding locations in finger two.…”
Section: Structure Of Dna Substrates For Annealing Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…There are five amino acids which differ between the two finger sequences. These include (finger one to finger two): F to W, N to K, I to Q, A to M, and N to D at positions 16,17,24,25, and 27 of finger one, respectively. NC point mutants were constructed where the amino acid residues in finger one were incrementally replaced by those at the corresponding locations in finger two.…”
Section: Structure Of Dna Substrates For Annealing Assaymentioning
confidence: 99%
“…Of the 14 amino acids that compose each finger, five differ between the two zinc fingers (in the pNL4-3 clone of HIV-1): (finger one to finger two): phenylalanine to tryptophan (F to W), asparagine to lysine (N to K), isoleucine to glutamine (I to Q), alanine to methionine (A to M), and asparagine to aspartic acid (N to D) at positions 16,17,24,25, and 27 of finger one, respectively. Presumably these differences underlie the much stronger helix destabilizing activity of finger one.…”
Section: Introductionmentioning
confidence: 99%
“…NC has been shown to function in several steps of viral replication, including genomic RNA maturation, reverse transcription, and integration. NC displays nucleic acid chaperone activity, catalyzing the melting, reannealing, and folding of nucleic acid into their most stable conformations (31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44). All of these have important implications in strand transfer and reverse transcription.…”
Section: And References Therein and Ref 2)mentioning
confidence: 99%
“…Recent studies have shown that NC may play a role in integration of the proviral DNA (18,(25)(26)(27). Also, NC sequences in the Gag precursor are a necessity for packaging of the RNA genome (28 -30) and the maturation of the genomic RNA dimer in the virion core (31,32). In vivo studies have specifically linked packaging activity to the zinc finger regions of the Gag (NC) precursor (33,34).…”
mentioning
confidence: 99%